2007
DOI: 10.1037/0735-7044.121.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves memory acquisition and retrieval in the Y-maze task: Relationship with hippocampal neurogenesis.

Abstract: Exercise improves memory acquisition and retrieval in the Y-maze task: Relationship with hippocampal neurogenesis van der Borght, K.; Havekes, Robbert; Bos, T.; Eggen, Bartholomeus; van der Zee, Eelke University of Groningen Enhanced physical activity is associated with improvements in cognitive function in rodents as well as in humans. The authors examined in detail which aspects of learning and memory are influenced by exercise, using a spatial Y-maze test combined with a 14-day exercise paradigm at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
151
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 64 publications
11
151
0
1
Order By: Relevance
“…This is consistent with the findings of previous studies showing that BDNF is increased after spatial learning and memory tasks (Mizuno et al, 2003). Radak et al reported that reduced oxidative damage in rat brain with voluntary exercise is associated with increased BDNF levels (Radak et al, 2001) and neurogenesis (Van der Borght et al, 2007). In addition, mutant BDNF and BDNF receptor blocker were associated with impaired spatial learning and memory formation in Morris maze and eight-arm radial maze, and LTP (Linnarsson et al, 1997;Minichiello et al, 1999).…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the findings of previous studies showing that BDNF is increased after spatial learning and memory tasks (Mizuno et al, 2003). Radak et al reported that reduced oxidative damage in rat brain with voluntary exercise is associated with increased BDNF levels (Radak et al, 2001) and neurogenesis (Van der Borght et al, 2007). In addition, mutant BDNF and BDNF receptor blocker were associated with impaired spatial learning and memory formation in Morris maze and eight-arm radial maze, and LTP (Linnarsson et al, 1997;Minichiello et al, 1999).…”
Section: Discussionsupporting
confidence: 84%
“…Taken together, this data indicates that physical exercise has a significant impact on the development of immature and mature neurons. Our findings of increased neurogenesis with physical exercise are in line with previous reports using adult and aged wild-type mice that found physical exercise augments the rate of hippocampal neuronal differentiation, maturation and survival [48][49][50][51][52]. Similarly, in the APP23 transgenic mice, physical exercise was able to increase the number of newborn granule cells in the dentate gyrus [21].…”
Section: Discussionsupporting
confidence: 82%
“…Beneficial effects of these therapies include improved learning and memory, 27,28 improved motor function, 13,16 and enhancement of proteins involved in brain plasticity such as BDNF, cAMP response-elementbinding protein, and synapsin-1. 11,27,29 -31 Consistent with these findings, we found that a challenging and graduated rehabilitation therapy consisting of running exercise and reach training significantly improved skilled reaching in the staircase task after focal ischemia in rats.…”
Section: Discussionmentioning
confidence: 99%